2012
DOI: 10.1103/physrevx.2.011003
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Semiconducting Nitrogen-Graphene Alloys

Abstract: The interaction between substitutional nitrogen atoms in graphene is studied by performing firstprinciples calculations. The effective nearest-neighbor interaction between nitrogen dopants is found to be highly repulsive because of the strong electrostatic repulsion between nitrogen atoms. This interaction prevents the full nitrogen-carbon phase separation in nitrogen-doped graphene. Interestingly, there are two relatively stable nitrogen-nitrogen pair configurations, whose stability can be attributed to the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
101
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 48 publications
(66 reference statements)
15
101
0
Order By: Relevance
“…To investigate this possibility, we calculated the frequency-dependent dielectric function from the summation over pairs of occupied and empty states without considering the local field effects, 49 and then the absorption coefficients as a function of photon energy were evaluated. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate this possibility, we calculated the frequency-dependent dielectric function from the summation over pairs of occupied and empty states without considering the local field effects, 49 and then the absorption coefficients as a function of photon energy were evaluated. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The method has been successfully applied in predicting crystal structures for various high-pressure systems including semiconducting phase of lithium, 16 and the single layer 2D structures. 22,23 The 2D materials are not necessarily planar. Their atomic layers may buckle in the perpendicular direction.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 In many applications, the limit of the N doping concentration in g-NG is important for both basic research and practical uses; however, it has not been found yet. Only isolated two-dimensional CN alloys were considered previously, such as C 12 N and C 3 N, 12 which are shown as smaller points on the diagram in Fig. 1, along with other two-dimensional BCN alloys considered theoretically.…”
mentioning
confidence: 99%
“…Smaller circles show other two-dimensional BCN systems considered previously. 3,[12][13][14][15][16][17][18][19][20] Mixing energies of the 2D carbon-nitrogen alloy were obtained using the cluster expansion (CE) method. 51 …”
mentioning
confidence: 99%